Field of study and financial problems: How economics reduces the risk of default - Kristoffer Balle Hvidberg (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2021)
This paper documents how extensive economic education can reduce the risk of getting into financial problems by comparing people who enter business and economics programs with people who enter other higher education programs. To identify the causal effect, I exploit GPA admission thresholds that quasi-randomize applicants near the thresholds into different programs. I find that admission to an economics education significantly reduces the probability of loan default by onehalf. This large reduction in the default probability is associated with changes in financial behavior, but it is not associated with differences in the level or stability of people's income.
Keywords: G51; G53; I23; 330; Financial Problems; Education; Regression Discontinuity; Financial Literacy